Digital Transformation in Public Organizations: An Applied Study on the Ministry of Health in the Kingdom of Saudi Arabia - Saqqat, Ahmad Adil (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to know the digital transformation in public organizations, and the study was applied to the Ministry of Health. The study relied on the analytical descriptive approach. The study sample consisted of (52) employees working in the Ministry of Health in the Kingdom of Saudi Arabia. The questionnaire was used as an appropriate tool for the study. The researcher reached several results, the most prominent of which are: The ministry's senior management provides sufficient support towards digital transformation and the appropriate time towards digital transformation efforts in all the ministry's transactions. digital. The study reached a number of recommendations, the most important of which are: Enhancing the support of the Ministry's senior management for digital transformation by providing the administration with a special budget to develop the quality of its electronic services as an entry point for digital transformation, and allocating the Ministry for an effective incentive system for distinguished human resources, which encourages the speed of transformation to apply management by electronic means.
Keywords: digital transformation; public organizations; Ministry of Health